If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = n + -4 Reorder the terms: -1 = -4 + n Solving -1 = -4 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -1 + -1n = -4 + n + -1n Combine like terms: n + -1n = 0 -1 + -1n = -4 + 0 -1 + -1n = -4 Add '1' to each side of the equation. -1 + 1 + -1n = -4 + 1 Combine like terms: -1 + 1 = 0 0 + -1n = -4 + 1 -1n = -4 + 1 Combine like terms: -4 + 1 = -3 -1n = -3 Divide each side by '-1'. n = 3 Simplifying n = 3
| 12y=21/4 | | 9(2x-6)=3(6x+1) | | 7(5+c)=6(c-1) | | -17+3y=51 | | (8f)/(6f) | | 8f/6f | | 6y-6=3y+9 | | n/2=12 | | 14+-8t=1328 | | 4(x+9)-4whenx=3 | | 9x+8=-64 | | -25-4c=17 | | -3p+7=5(12p+6) | | 7q/7=84 | | 5x+8(1/3x+8)=-5 | | K-8-1=3+4k+k | | 3+8x=63 | | 7+3m-2=8m+11-4m | | 8t+16=3t-6t+8t-34 | | 1/7(x+7)=1/14(2x+14) | | a/6=20 | | 2/3y-1/6y+4=18 | | 3-4n=-12-7n | | 5n/10=25 | | 13=3w-5 | | 6b+3=7+2b | | 5/6k=7/18 | | x/14-5x+2/49=3x-4/7 | | 8(8-7a)=176 | | 1/n=3/9 | | 10(x+1)=10 | | 9=13-x+5x |